Mechanistic study and protein engineering of a dye-decolorizing peroxidase from Thermomonospora curvata for enhanced and expanded functions - Khadka, Samiksha (My University, 2025)
The growing demand for efficient and sustainable biocatalysts has intensified efforts to engineer enzymes with improved catalytic performance, substrate specificity, and stability. Dye-decolorizing peroxidases (DyPs), a versatile class of heme enzymes, are particularly attractive for industrial and environmental applications, including lignin valorization and dye degradation. However, their catalytic potential is often limited by intrinsic structural and electronic constraints. This dissertation presents a comprehensive, multi-pronged strategy to enhance the catalytic efficiency and functional diversity of the A-class DyP from Thermomonospora curvata (TcDyP) through rational engineering, cofactor substitution, and genetic code expansion. In the first part of this work, we identified a key surface-exposed loop residue, Glu293, as a target for tuning substrate access and radical stability. Replacing E293 with glycine (E293G) enhanced peroxidase activity toward small-sized substrates, likely due to increased heme accessibility through an expanded substrate channel, as confirmed by our crystal structure. Surprisingly, the histidine substitution (E293H) led to a significant improvement in activity, attributed to the establishment of an alternative mode of radical relay pathway, supported by evidence from protein crosslinking, radical trapping, and LC-MS/MS studies. Structural and transient kinetic studies further revealed that this mutation let to the surface radical formation via proton-coupled electron transfer pathways, likely through interactions with catalytic residues Asp220 and Arg327. Our discovery underscores the importance of dynamic, surface-accessible residues in modulating enzyme function and radical stabilization. Building on this scaffold engineering, the second chapter explores the introduction of abiological reactivity through cofactor modification and reconstitution. Incorporation of an iridium-based porphyrin cofactor (Ir(Me)-MPIX) into TcDyP enabled stereodivergent carbene transfer reactions specifically, the cyclopropanation of styrene with ethyl diazoacetate, demonstrating the feasibility of repurposing DyPs for new chemical transformations. The enzyme scaffold not only accommodated the artificial metal center but also influenced diastereo- and enantioselectivity, which was further improved through mutagenesis. These findings establish TcDyP as a promising platform for artificial metalloenzyme development. In the final chapter, genetic code expansion was employed to incorporate a non-canonical amino acid, N[superscript delta]-methyl histidine (NMH), as the proximal heme ligand. This substitution allowed systematic investigation of the conserved and critical Asp-His-Fe triad in heme peroxidases and its role in tuning redox potential, intermediate stability, and catalytic activity. Although NMH incorporation did not drastically alter the overall protein structure, it modulated the Fe–His bond strength and slowed the regeneration of the enzyme resting state, offering new insights into the dynamics of electron transfer and radical generation in DyPs. Together, these studies highlight how precise modifications at the flexible loop, cofactor, and proximal ligand can dramatically enhance and expand the reactivity and robustness of DyPs. This work provides a foundation for the rational design of next-generation peroxidases tailored for synthetic, industrial, and environmental biocatalysis.
Keywords: Protein engineering